Proposed Electrical System Design of Streetlights at Megadike Access Road (ELEKTRIKA- Journal of Electrical Engineering, 2023)
Due to the absence of streetlights, it is unsafe for drivers to travel during the night in the current state of Mega Dike. The lack of streetlights causes low visibility for drivers, which is one of the major factors that causes road crashes. Thus, this study aims to propose an electrical system design of streetlights at the Mega Dike Access Road. In order to plan an electrical system design, the proponents would take in consideration the following parameters; Illumination formula for pole spacing; voltage drop calculation; economic analysis; and simulation of the system. The results will be presented in tabulated form for the respective parameters. The study examines five (5) different cases, taking into account different lamp wattages, voltage drop considerations, and cost analysis. The study would abide with the standards set by the Philippine Electrical Code (PEC) and Department of Energy (DOE). The goal of the proposed streetlights is to provide additional security for drivers on the Mega Dike Access Road by improving visibility and reducing the risk of road crashes caused by low visibility. Generally, the significance of streetlights is needed in Mega Dike Access Road in order to address the issue of low visibility for drivers and improve overall road safety in the area.